Infection dynamics of Posthodiplostomum sp. (Digenea: Diplostomidae) in first and second intermediate hosts from an Andean Patagonian lake (Argentina) - Ritossa, Luciano (2014)
In Argentinean Patagonia, a species of the genus Posthodiplostomum has been reported infecting populations of the snail Anisancylus obliquus and the galaxiid fish Galaxias maculatus (small puyen), meanwhile adults would develop in piscivorous birds. The aim of the present work was to describe the seasonal dynamics of this parasite in the intermediate hosts inhabiting a small, shallow Patagonian Andean lake. Samples of snails and fish from Patagua Lake (40° 46' S - 71° 36' W) were collected monthly from October 2010 to March 2011. The larval infection of Posthodiplostomum sp. increases in spring. Snails were infected from November to January, with the highest prevalence in December (8.2%), decreasing in January (3.1%). In fish, prevalence ranged between 70% (November) and 100% (December to March). The highest infection values were recorded in larger fish, while the small fish with sizes less than 40 mm exhibited low infection levels. So, we can infer that the life cycle of Posthodiplostomum sp. in Patagonia shows a seasonal pattern, with larval development during spring, when cercariae emerge from larger snails, resulting in a higher prevalence of fish in the littoral.